The Future of Work Challenges and Prospects for Organisations, Jobs and Workers - Lynn, Theo; Rosati, Pierangelo; Conway, Edel; van der Werff, Lisa (Palgrave Studies in Digital Business & Enabling Technologies, 2023)
The COVID-19 pandemic accelerated the adoption of new forms of working and new working arrangements largely enabled by technology. The Future of Work is a projection of how work, working, workers and the workplace will evolve in the years ahead from the perspective of different actors in society, influenced by technological, socio-economic, political, and demographic changes. This open access book is a timely exploration of some of the challenges and prospects for the future of work from two main perspectives: how work is changing and how to prepare for work in the future. An evidence-based assessment of these topics offers some critical perspectives that challenge old assumptions and opens up emerging trends and possibilities for work in the future. As part of the Palgrave Studies in Digital Business & Enabling Technologies series, this book is an essential resource for academics of Business, Human Resource Management, Organisational Psychology and Industrial Relations,as well as practitioners and policy makers. Theo Lynn is Full Professor of Digital Business at DCU Business School, Ireland. He is Series Editor on the Palgrave Studies in Digital Business & Enabling Technologies. Pierangelo Rosati is Associate Professor of Digital Business & Society at the University of Galway, Ireland and is Series Editor on the Palgrave Studies in Digital Business & Enabling Technologies. Edel Conway is Full Professor of HRM and Organisational Psychology and Associate Dean of Research at DCU Business School, Ireland. She is an organisational psychologist with expertise in the areas of Human Resource Management and Organisational Change. Lisa van der Werff is Associate Professor of Organisational Psychology at DCU Business School, Ireland and Co-Director of the Irish Institute of Digital Business.She is an organisational psychologist and specialises in trust research.